2020
DOI: 10.1051/0004-6361/201937299
|View full text |Cite
|
Sign up to set email alerts
|

Processes governing the VIS/NIR spectral reflectance behavior of lunar swirls

Abstract: We investigated six bright swirls associated with magnetic anomalies of variable strength using Chandrayaan-1 Moon Mineralogy Mapper (M3) hyperspectral image data. We examined the 3 μm absorption band generally ascribed to solar wind-induced OH/H2O and spectral trends in the near-infrared wavelength range at on-swirl and off-swirl locations. We found that the 3 μm absorption band i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 71 publications
(126 reference statements)
3
35
1
Order By: Relevance
“…Similar to previous studies (e.g., Li and Garrick-Bethell 2019), recent results by Hess et al (2020) indicate a weaker 3-µm band at the swirl locations than on the surrounding surface. This finding supports the assumption that the magnetic field locally reduces the flux of solar wind protons, leading to a reduced rate of OH/H 2 O formation in the regolith.…”
Section: Local Anomaliessupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to previous studies (e.g., Li and Garrick-Bethell 2019), recent results by Hess et al (2020) indicate a weaker 3-µm band at the swirl locations than on the surrounding surface. This finding supports the assumption that the magnetic field locally reduces the flux of solar wind protons, leading to a reduced rate of OH/H 2 O formation in the regolith.…”
Section: Local Anomaliessupporting
confidence: 90%
“…This would lead to soil compaction and, according to the model by Hapke (2008), increased surface albedo without changing the mafic band depths and spectral slope. Additionally, the cometary gas may also remove the uppermost, highly matured regolith layer and reveal immature material, which would be consistent with the observation by Hess et al (2020) that spectra indicating a low surface maturity occur at all studied swirls. Using spectra of the lunar surface acquired by the Yutu rover at different distances from the Chang'E-3 lander, Wu and Hapke (2018) demonstrated that a landing rocket jet causes exactly this effect.…”
Section: Local Anomaliessupporting
confidence: 90%
See 1 more Smart Citation
“…On-swirl regions in our study areas are higher in feldspar and orthopyroxene (Lemelin et al, 2019) and are depleted in FeO (Lemelin et al, 2019), TiO 2 (Sato et al, 2017), and OH (Hess et al, 2020;Kramer et al, 2011a). Of particular interest, is the abundance of submicroscopic (≤1 μm) iron particles.…”
mentioning
confidence: 83%
“…Spectral parameters in the UV (e.g., [3,4]) or in the NIR (e.g., [5]) can also be used to estimate the elemental abundances, but should be used with care. For example, according to the TiO 2 maps of Sato et al [4] the swirl Reiner Gamma is deprived of TiO 2 compared to its surroundings, which is physically implausible, as the optical differences are likely due to a difference in maturity and/or compaction [53]. Setting a prior, however, does not rule out solutions that do not confirm with prior knowledge, as long as the probability of the prior does not become zero.…”
Section: Priormentioning
confidence: 99%